Goal-Based Evaluation Model of the Vocational Development Program for Narcotics Inmates at Class IIA Lombok Barat Correctional Facility - Aldy Ferdiawan; Wido Cepaka Warih (Universitas Merdeka Madiun, 2026)
Abstract Introduction to the Problem: Vocational development programs in correctional institutions are designed to equip inmates with life skills to reduce recidivism and support social reintegration. However, the effectiveness of the program at Class IIA Lombok Barat Correctional Facility, particularly for narcotics inmates, has not been comprehensively evaluated, making it difficult to assess the achievement of its intended objectives. Purpose/Study Objectives: This study aims to evaluate the implementation of the vocational development program for narcotics inmates at Class IIA Lombok Barat Prison and to identify the challenges faced during its execution. Design/Methodology/Approach: The research adopts a qualitative method with a goal-based evaluation approach, employing in-depth interviews, participatory observation, and document analysis. The data were analyzed inductively to examine the alignment between program objectives and actual outcomes. Findings: The results reveal that program effectiveness is constrained by limited availability of tools, materials, and facilities, which hinder vocational training activities such as wood carving, culinary arts, welding, and batik-making. Inmates generally require intensive guidance as their basic skills are underdeveloped. While the program positively enhances productivity, patience, and self-confidence, its connection to post-release employment opportunities remains weak. Additional challenges include shortages of resources, limited training time, and internal issues such as inmate motivation and discipline. These findings highlight the importance of improving funding systems, resource management, and individualized approaches to ensure program sustainability and strengthen rehabilitation outcomes. Paper Type: Research Article Keywords: Vocational Development; Narcotics Inmates; Correctional Facility; Rehabilitation; Social Reintegration